Certificateless multi-source signcryption with lattice - Huifang Yu; Jiafeng Shi (Journal of King Saud University. Computer and information sciences, 2022)
Network coding can improve network transmission performance and reduce data transmission delay. However, the nodes in network are vulnerable to pollution attacks. Previous network coding schemes are based on difficult problems in number theory and cannot resist the quantum computing attacks. Hence, certificateless multi-source signcryption with lattice (LCL-MSSC) is devised for network coding, it uses common public key to verify the combination ciphertext from different source node users. Based on learning with errors and inhomogeneous small integer solution problems, LCL-MSSC is unforgeable under the adaptive chosen-message attacks and indistinguishable under the adaptive chosen-ciphertext attacks; in addition, it can resist the pollution attacks and quantum computing attacks. Efficient LCL-MSSC has broad application prospect in UAV wireless communication network, mobile wireless network, wireless sensor network or cyberspace security.